Influenza vaccination for healthcare workers in the UK: appraisal of systematic reviews and policy options. Issue 9 (13th September 2016) - Kliner, Merav; Keenan, Alex; Sinclair, David; Ghebrehewet, Sam; Garner, Paul
Abstract : Background: The UK Department of Health recommends annual influenza vaccination for healthcare workers, but uptake remains low. For staff, there is uncertainty about the rationale for vaccination and evidence underpinning the recommendation. Objectives: To clarify the rationale, and evidence base, for influenza vaccination of healthcare workers from the occupational health, employer and patient safety perspectives. Design: Systematic appraisal of published systematic reviews. Results: The quality of the 11 included reviews was variable; some included exactly the same trials but made conflicting recommendations. 3 reviews assessed vaccine effects in healthcare workers and found 1 trial reporting a vaccine efficacy (VE) of 88%. 6 reviews assessed vaccine effects in healthy adults, and VE was consistent with a median of 62% (95% CI 56 to 67). 2 reviews assessed effects on working days lost in healthcare workers (3 trials), and 3 reported effects in healthy adults (4 trials). The meta-analyses presented by the most recent reviews do not reach standard levels of statistical significance, but may be misleading as individual trials suggest benefit with wide variation in size of effect. The 2013 Cochrane review reported absolute effects close to 0 for laboratory-confirmed influenza, and hospitalisation for patients, but excluded data on clinically suspected influenza and all-cause mortality, which had shown potentially important effects in previous editions. A more recent systematic review reports these effects as a 42% reduction in clinically suspected influenza (95% CI 27 to 54) and a 29% reduction in all-cause mortality (95% CI 15 to 41). Conclusions: The evidence for employer and patient safety benefits of influenza vaccination is not straightforward and has been interpreted differently by different systematic review authors. Future uptake of influenza vaccination among healthcare workers may benefit from a fully transparent guideline process by a panel representing all relevant stakeholders, which clearly communicates the underlying rationale, evidence base and judgements made.